Identification of a Novel HtrA1-susceptible Cleavage Site in Human Aggrecan: EVIDENCE FOR THE INVOLVEMENT OF HtrA1 IN AGGRECAN PROTEOLYSIS IN VIVO - Chamberland, Angela (American Society for Biochemistry and Molecular Biology, 2009)
Mass spectrometry-based proteomic analyses performed on cartilage tissue extracts identified the serine protease HtrA1/PRSS11 as a major protein component of human articular cartilage, with elevated levels occurring in association with osteoarthritis. Overexpression of a catalytically active form of HtrA1, but not an active site mutant (S328A), caused a marked reduction in proteoglycan content in chondrocyte-seeded alginate cultures. Aggrecan degradation fragments were detected in conditioned media from the alginate cultures overexpressing active HtrA1. Incubation of native or recombinant aggrecan with wild type HtrA1 resulted in distinct cleavage of these substrates. Cleavage of aggrecan by HtrA1 was strongly enhanced by HtrA1 agonists such as CPII, a C-terminal hexapeptide derived from the C-propeptide of procollagen IIα1 (i.e. chondrocalcin). A novel HtrA1-susceptible cleavage site within the interglobular domain (IGD) of aggrecan was identified, and an antibody that specifically recognizes the neoepitope sequence (VQTV(356)) generated at the HtrA1 cleavage site was developed. Western blot analysis demonstrated that HtrA1-generated aggrecan fragments containing the VQTV(356) neoepitope were significantly more abundant in osteoarthritic cartilage compared with cartilage from healthy joints, implicating HtrA1 as a critical protease involved in proteoglycan turnover and cartilage degradation during degenerative joint disease.